The Arrangement Of Rights And Obligations In The Implementation Of Akad Syirkah Mudharabah Ayam Geprek Sa’i In Yogyakarta - Ayu, Indah Maulida Sekar; Musjtari, Dewi Nurul (Media of Law and Sharia, 2020)
This research discusses about Akad Syirkah Mudharabah Ayam Geprek Sa'i conducted between the brand owner and the capital owner, where the agreement is an alliance that uses Akad Syirkah Mudharabah and a profit-making system with the aim of conducting a business activity of fast food restaurant culinary business. In the Akad Syirkah Mudharabah Ayam Geprek Sa'i there are also weaknesses that cause problems in its implementation, including vagueness about the arrangement of rights and obligations for the parties itself. The purpose of this research is to find the arrangement of rights and obligations in the implementation of Akad Syirkah Mudharabah Ayam Geprek Sa'i in Yogyakarta. This research was conducted using empirical normative research methods that are based on the regulation of Akad Syirkah Mudharabah Ayam Geprek Sa'i then compare it by looking at the facts that occur and looking at the prevailing laws and regulations in Indonesia and arranged using qualitative methods, with using systematically arranged and descriptive explanation. The results of this research is the arrangement of rights and obligations stipulated in Article 6 of the Akad Syirkah Mudharabah Ayam Geprek Sa'i in Yogyakarta, but have not yet proceeded in accordance with the existing regulations that has been agreed in the agreement